The impact of working capital management on corporate profitability and liquidity: evidence from the automobile and e-commerce industries - Przygoda, Robert (2022)
This paper empirically analyses key differences in Working Capital Management (WCM) in the automobile and e-commerce industries. Furthermore, the impact of WCM on Profitability and Liquidity is examined. The results have shown that there are significant differences in WCM between industries, as measured by the Cash Conversion Cycle (CCC). At the same time, differences in the financial structure could also be identified. The multivariate analysis showed that there is a significant negative relationship between CCC and Return on Assets in the automobile industry, but not e-commerce. Moreover, a significant relation between the CCC components and the Quick Ratio was demonstrated.